Causes and Consequences of Physiological Load of Workers in Grape Cultivation Activities - Kumari, Savita; Mehta, Manju (Indian Journal of Extension Education, 2020)
The aim of this study was to find out the causes and consequences of physiological load of workers in grapeÂ cultivation activities. The study was conducted with 15 respondents who were engaged on grapes cultivationÂ activities. Physical fitness was determined by calculating the physical parameters i.e. height, weight, BMI,Ectomorphic, Mesomorphic type body. Maximum respondents were in grape group of above 26 years. Hence, a continuous awkward standing posture and adverse environmental and working conditions increase andÂ decrease productivity of grape orchard workers. The change in environmental temperature and physiological load greatly affect the workers. The physical characteristics comprising age, height, weight, body mass index, physical fitness index play a major role for the physical health and workload of the health of grape orchard workers. The physiological load was found highest for pruning followed by harvesting. The least physiologicalÂ load was for plant protection